L’apprentissage par cœur, au-delà de la polémique - Yvan Abernot; Jacques Audran; Éric Penso (Éducation et Socialisation)
In view of the last governmental orientations, « learning by heart » gains a renewed interest. This is not going without any controversy. Our study proposes a reflexive approach, but also an investigation that tries to bear the hypothesis of a complementarity between learning by heart and comprehension.After having defined the concept, we try to classify the objects and functions of learning by heart to make emerge its advantages and risks.To support this problematic, we have analyzed the answers of thirty four elementary school teachers who position themselves and enrich the reflexion.It seems that beyond the representations sometimes dogmatic, or even ideological, of specialists and partners of education, the process of learning by heart could take part in an ambitious project, as long as it is not reduced to psittacism or evaluation facilities.